Impacto del cambio climático en las cadenas productivas del café: Presentación en Junta Nacional del café de Peru Gira de Aprendizaje a Colombia - Cali, Colombia - Lundy, Mark M.; Bunn, Christian (2016)
What is the projected impact of climate change on coffee value chains globally and in Central America. What can be done to improve the resilience of these production systems to the projected impact of climate change?